Scalable Synthesis of a Chiral Selenium π-Acid Catalyst and Its Use in Enantioselective Iminolactonization of β,γ-Unsaturated Amides - Otsuka, Yuta; Shimazaki, Yuto; Nagaoka, Hitoshi; Maruoka, Keiji; Hashimoto, Takuya (Synlett, 2019)
Chiral selenium π-acid catalysis has for a long time been lagging behind other areas of asymmetric catalysis due to a lack of highly enantioselective catalysts. In this regard, we recently developed the first chiral selenium π-acid catalyst which performs the oxidative cyclization of β,γ-unsaturated carboxylic acids with high enantioselectivities. We report herein our improved synthesis of this chiral selenium catalyst, which allows access to a large quantity of the catalyst as the diselenide. In addition, the catalyst is tested in the oxidative cyclization of N-methoxy β,γ-unsaturated amides to give iminolactones with high enantioselectivities.
Keywords: selenium; diselenide; asymmetric catalysis; oxidative cyclization; iminolactones